Evaluating the use of multiteam systems to manage the complexity of inpatient falls in rural hospitals. (18th June 2019) - Jones, Katherine J.; Skinner, Anne; Venema, Dawn; Crowe, John; High, Robin; Kennel, Victoria; Allen, Joseph; Reiter‐Palmon, Roni
Abstract: Objective: To evaluate the implementation and outcomes of evidence‐based fall‐risk‐reduction processes when those processes are implemented using a multiteam system (MTS) structure. Data Sources/Study Setting: Fall‐risk‐reduction process and outcome measures from 16 small rural hospitals participating in a research demonstration and dissemination study from August 2012 to July 2014. Previously, these hospitals lacked a fall‐event reporting system to drive improvement. Study Design: A one‐group pretest‐posttest embedded in a participatory research framework. We required hospitals to implement MTSs, which we supported by conducting education, developing an online toolkit, and establishing a fall‐event reporting system. Data Collection: Hospitals used gap analyses to assess the presence of fall‐risk‐reduction processes at study beginning and their frequency and effectiveness at study end; they reported fall‐event data throughout the study. Principal Findings: The extent to which hospitals implemented 21 processes to coordinate the fall‐risk‐reduction program and trained staff specifically about the program predicted unassisted and injurious fall rates during the end‐of‐study period (January 2014‐July 2014). Bedside fall‐risk‐reduction processes were not significant predictors of these outcomes. Conclusions: Multiteam systems that effectively coordinate fall‐risk‐reduction processes may improve the capacity of hospitals to manage the complex patient, environmental, and system factors that result in falls.